Anti‐CRISPRs: The natural inhibitors for CRISPR‐Cas systems. Issue 2 (29th May 2019) - Zhang, Fei; Song, Guoxu; Tian, Yong
Abstract: CRISPR (clustered regularly interspaced short palindromic repeats)‐Cas (CRISPR associated protein) systems serve as the adaptive immune system by which prokaryotes defend themselves against phages. It has also been developed into a series of powerful gene‐editing tools. As the natural inhibitors of CRISPR‐Cas systems, anti‐CRISPRs (Acrs) can be used as the "off‐switch" for CRISPR‐Cas systems to limit the off‐target effects caused by Cas9. Since the discovery of CRISPR‐Cas systems, much research has focused on the identification, mechanisms and applications of Acrs. In light of the rapid development and scientific significance of this field, this review summarizes the history and research status of Acrs, and considers future applications.